Assessing productive lands as viable habitat for huemul in patagonia. Issue 3 (1st February 2016) - Sandvig, Erik M.; Espinaze, Marcela P.A.; Marín‐Vial, Paula; Corti, Paulo
ABSTRACT: The creation of protected areas has been the main strategy to counter loss and fragmentation of habitats for large mammals, but these areas by themselves cannot guarantee species' conservation. Forestry plantations can provide habitat for a large range of species. However, studies assessing the impact of forestry plantations on large mammals are scarce. Our objective was to identify the environmental variables that explained the presence of the endangered huemul deer ( Hippocamelus bisulcus ) in an area with mixed pine plantation and native forest in the Chilean Patagonia. Occupancy models using data collected from camera traps indicated higher occupancy in plantation areas (0.70) than in native forest (0.50). The main variable explaining the presence of the huemul in both forest types was the understory cover between 21 cm and 50 cm in height. By maintaining understory cover, plantations provide a suitable complementary habitat for the forest‐dwelling huemul. © 2016 The Wildlife Society.